PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT YAMAN PANGAN INDONESIA DI PASAR KEMIS KABUPATEN TANGERANG - Muhamad Dika Alam; Henni Marlinah (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the effect of recruitment and training on employee performance at PT Yaman Pangan Indonesia in Pasar Kemis, Tangerang Regency. The method used is quantitative. The sampling technique used the Slovin formula and a sample of 107 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that recruitment has a significant effect on employee performance with a coefficient of determination value of 43.0% and the hypothesis test obtained t count > t table or (8.908 > 1.983). Training has a significant effect on employee performance with a coefficient of determination value of 40.7% and hypothesis testing obtained t count > t table or (8.489 > 1.983). Recruitment and training simultaneously have a significant effect on employee performance with the regression equation Y = 7.624 + 0.412X1 + 0.396X2. The coefficient of determination value is 57.1% while the remaining 42.9% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (69.114 > 2.690).